A New File Format to Describe Fiber-reinforced Composite Workpiece Structure for Additive Technology Machines. (2015) - Shchurova, E.I.; Shchurova, A.V.
Abstract: Additive manufacturing is mostly used to produce homogeneous parts. Soon fiber-reinforced composite materials which let to crowd fibers at the maximal stress locations will be available for additive manufacturing. However, the existing file formats such as STL-format describing the composites on micro-level require incredible data volume. To overcome this problem the authors propose a file format with a description of domains, representative volume elements, and voxels in the first file section. The second section includes the information on the part surfaces. The third one consists of the polynomial coefficients for domains on each part layer. This approach gives a real opportunity to produce FRC parts by additive manufacturing.